Reclaiming the politics of South-South cooperation - Muhr, T. (Globalizations, 2023)
Framed by the North–South conflict, this article conducts a historico-conceptual analysis of the politics of South-South cooperation (SSC) from a decolonial Global South perspective. Based on documentary analysis and a review of academic SSC literature, three distinct periods of SSC post-1945 are identified: Concertation (1945–1981); Containment (1981–1995); and Cooptation vs Confrontation (1995–present). This periodization complements previous endeavours of its kind, whereby the rationale here is that a historical understanding of SSC politics and neo-colonial/imperialist counter-politics is indispensable for emancipatory social praxis. With co-optation of SSC backed by coercion as the Global North’s contemporary tactic within the strategy of re-Westernisation, I argue for the Global South to reclaim SSC as a strategy to move from delinking as de-Westernisation towards delinking as decoloniality in the context of crisis of the capitalist world order.